2013
DOI: 10.1007/s11250-013-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian evaluation of Girolando (Holstein × Gir) heifers submitted to a GnRH–PGF2α–GnRH protocol in the dry or rainy seasons in the tropical savannah

Abstract: The Girolando breed is used in pasture-based dairy production systems in Brazil to associate the high production of Bos taurus to the rusticity and thermal adaptation of Bos indicus. This study was designed to evaluate the physiological response to a gonadotropin-releasing hormone (GnRH)-prostaglandin F2α (PGF2α)-GnRH protocol to synchronize the ovulation in 40 Girolando heifers of a pasture-based dairy production system and its relationships with the temperature and humidity index (THI) during the dry (DS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The increase in WP of cows that give birth during the RS could result from the indirect effect of a significant increase in THI (81.5 vs. 79.9, P < 0.001). A similar effect has been observed in Brazil (Bilego et al 2013). Several studies have shown the negative effects of heat stress on BCS through a reduction in intake capacity, follicular growth (Kornmatitsuk et al 2008), the resumption of PP ovarian cyclicity (Kornmatitsuk et al 2008;Rensis and Scaramuzzi 2003), and on the quality of heat detection (Fekadu et al 2011;Kornmatitsuk et al 2008).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The increase in WP of cows that give birth during the RS could result from the indirect effect of a significant increase in THI (81.5 vs. 79.9, P < 0.001). A similar effect has been observed in Brazil (Bilego et al 2013). Several studies have shown the negative effects of heat stress on BCS through a reduction in intake capacity, follicular growth (Kornmatitsuk et al 2008), the resumption of PP ovarian cyclicity (Kornmatitsuk et al 2008;Rensis and Scaramuzzi 2003), and on the quality of heat detection (Fekadu et al 2011;Kornmatitsuk et al 2008).…”
Section: Discussionsupporting
confidence: 69%
“…The CRFS (58%) is lower than that of Holstein crossbred heifers in Thailand (68%) (Buaban et al 2015). These differences can be explained by the effect of nutritional (Le Cozler et al 2009) or environmental factors (heat stress) (Bilego et al 2013). Our study observed a significant decrease in AFS and AC according to year of birth.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Bilego et al . 21 found that THI interfered with follicular and luteal dynamics and the response of heifers to the GnRH-PGF 2α treatment, leading to reduced pregnancy after insemination. Ghuman et al .…”
Section: Discussionmentioning
confidence: 99%